Methods of Using Fuzzy Interval Logic During Processing of Space States of Complex Biophysical Objects - Lyashenko, V.; Syed Khalid Mustafa; Tvoroshenko, I.; M. Ayaz Ahmad (WARSE, 2020)
This article proposes a technique for using fuzzy interval logic during multi-stage processing of state spaces of complex biophysical objects in the medical system HEALTH. The proposed method of selecting the best diagnoses in the context of fuzzy background information was used to solve the practical problems of computer medical фdiagnostics. The theoretical and practical results formulated are the basis for the construction of systems and tools for computational intelligence. The diagnostic system is implemented on the basis of modern information technologies and computers. The presented computerized medical diagnostics system can be used in medical practice for the diagnosis of cardiovascular diseases, planning of health events and conducting of social and hygienic monitoring in medical institutions. Laboratory operation of fuzzy intellectual system HEALTH confirmed the high probability of making objective decisions in the medical subject area.
Keywords: Fuzzy Interval Logic; State of Space; Decision Making; Confidence Factor